2017
DOI: 10.5424/sjar/2017153-10271
|View full text |Cite
|
Sign up to set email alerts
|

Yield, flesh parameters, and proximate and fatty acid composition in muscle tissue of wild and cultured Vieja Colorada (Cichlasoma festae) in tropical Ecuadorian river

Abstract: This study was conducted to determine the composition of cultured and wild Cichlasoma festae in Ecuador. The mean slaughter yield and dress-out were similar for cultured and wild specimens and the average fillet fat content for cultured fish was significantly higher compared to the wild fish. The pH, fillet color, drip loss and coked loss were similar between populations. Significant differences were found in protein, lipid and ash content in both studied populations. This study showed that saturated fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
2
4
2
2
Order By: Relevance
“…Drip loss resulted similar to the obtained by González et al (2017), although lower than those reported by Intarak et al (2015) in Panga fish (Pangasius bocourti Sauvage), who obtained values from 4.88% to 2.88%, with significant decreases as live weight increased. None of the studied factors, rearing system or sex, had significant influence on drip loss.…”
Section: Flesh Quality and Proximate Compositionsupporting
confidence: 77%
See 1 more Smart Citation
“…Drip loss resulted similar to the obtained by González et al (2017), although lower than those reported by Intarak et al (2015) in Panga fish (Pangasius bocourti Sauvage), who obtained values from 4.88% to 2.88%, with significant decreases as live weight increased. None of the studied factors, rearing system or sex, had significant influence on drip loss.…”
Section: Flesh Quality and Proximate Compositionsupporting
confidence: 77%
“…In the first 12 hours post mortem, pH values were lower in wild specimens than in cultivated ones (0.83 vs. 0.59), in accordance with Robb et al (2000) and Roth et al (2009) who reported that muscle pH displayed a rapid decline during the aforementioned period. However, this drop was linear and progressive, in disagreement with González et al (2017), who had indicated a harsh drop during the first 2 hours post mortem. Even though pH values were adjusted by the temperature sensor of the pHmetre used, temperature may have generated differences in pH.…”
Section: Flesh Quality and Proximate Compositioncontrasting
confidence: 56%
“…Similar results for tilapia from the local fish markets in Poland were reported by Usydus et al (2011) who found 35.4% SFA, 33.1% MUFA, 31.5% PUFA, 9.9% n-3 and 21.6% n-6. The fatty acid profile of fish dependent on the diet, environmental conditions and production systems (Bogard et al, 2015;Gonz alez et al, 2017;Matos et al, 2019). The long-chain fatty acid erucic acid detected in wild and pond-cultured tilapia, and the concentration is 5.2% and 3.49% respectively.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…This, therefore, suggests that M. rume, L. senegalensis and C. gariepinus may be a better export product in terms of fillet yield compared to S. nigrita or B. bajad . Generally, the edible portion of fish depends on several factors such as species, sex and size, the structural anatomy of the fish and farming conditions ( Alinezhad 2004 ; González et al 2017 ). Of all the factors mentioned above, differences in species as it relates to structural anatomy are most likely the culprit of the observable differences reported in the current study.…”
Section: Resultsmentioning
confidence: 99%